2001
DOI: 10.1046/j.0007-1323.2001.01875.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the number of lymph nodes examined on staging of gastric cancer

Abstract: The number of lymph nodes examined did not significantly affect node staging of gastric cancer as long as at least 15 nodes were examined. For stage IIIB, more than 15 lymph nodes may be required for optimal staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
108
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 20 publications
2
108
1
2
Order By: Relevance
“…According to the JGCA data, cumulative 5-year survival of stage IV patients was 15.3%, 2 and Korean data also showed similar results with 18%. 3 Moreover, among all stage IV patients, 4% to 9% of them are said to be too advanced with no chance of curative surgery and their prognosis is absolutely poor showing less than 10% at 3 years after diagnosis. 16 JGCA suggests extended surgery or palliative surgery as clinical practice and reduction surgery as a clinical study for stage IV patients (T4 and N3 patients are classified as stage IV in this suggestion).…”
Section: Discussionmentioning
confidence: 99%
“…According to the JGCA data, cumulative 5-year survival of stage IV patients was 15.3%, 2 and Korean data also showed similar results with 18%. 3 Moreover, among all stage IV patients, 4% to 9% of them are said to be too advanced with no chance of curative surgery and their prognosis is absolutely poor showing less than 10% at 3 years after diagnosis. 16 JGCA suggests extended surgery or palliative surgery as clinical practice and reduction surgery as a clinical study for stage IV patients (T4 and N3 patients are classified as stage IV in this suggestion).…”
Section: Discussionmentioning
confidence: 99%
“…For example, with regard to the mucin phenotype, MUC1 and MUC5AC expression was less frequent in cardia carcinomas than in non-cardia carcinomas [16] . Therefore, lymph node status mainly depends on routine pathological examinations, previously based on the anatomical station of metastatic lymph nodes, and is classified by the number of metastatic regional lymph nodes [17][18][19] . The problem of lymph node classification based on number of metastatic ones is the stage migration, induced by larger lymph nodes dissected.…”
Section: Discussionmentioning
confidence: 99%
“…There are several retrospective studies demonstrating that more extensive lymphadenectomies are correlated with longer survival. A study of 4,789 patients at Seoul National University Hospital found that, for patients with stage IIIB disease, those who had Ͼ35 lymph nodes examined had better survival than those who had Ͻ20 nodes examined [43]. The German Gastric Carcinoma Study Group found, in an analysis of 1,654 patients, that those patients who underwent a radical lymphadenectomy (Ͼ25 lymph nodes) had a significantly higher survival rate than patients who had a standard lymph node dissection for stage II or stage IIIA tumors [37,44].…”
Section: Potential Benefits Of More Extensive Lymphadenectomiesmentioning
confidence: 99%